GAME OF THE GENERALS: GAME APPLICATION OF ALPHA-BETA PRUNING ALGORITHM. - Pagtalunan, Grace M. 4 0 16; 5 (2005)
Abstract This study was conducted by the researches by searching for documents that can help the study, analyzing them and constructing ways to solve problems that are found. The topic Alpha-Beta Pruning Algorithm was chosen by the researchers because of the rapidly growing game world today. Developing a better algorithm with the basis of the Alpha-Beta Pruning Algorithm is the main goal of this study. In this study we emphasized the use of Alpha-Beta Pruning Algorithm in the game called Game of the General. In this set-up of the given application the researchers seek for the way to solve the anomalies of the said algorithm and at the same time fitting it to the game application. You can see in this study how the researchers added functions and ran around the algorithm to make it fit for the game application. Since the algorithm as know to be the best algorithm for board games it was hard to find room for enhancement. The main challenge was to fit this algorithm to the application. Since the game application proposed has a different game play than the usual board game the researchers seek for a way to make the algorithm work with the game. With this anomaly the researchers decided to make assumption inserted in the algorithm.
Thesis (Undergraduate) Pamantasan ng Lungsod ng Maynila 2005.;Bachelor of Science in Computer Science.
Keywords: 2 -- 0; 6; 20; 20; 2